Structure of exoplanets - Spiegel, David S. (National Academy of Sciences, 2014)
The hundreds of exoplanets that have been discovered in the past two decades offer a new perspective on planetary structure. Instead of being the archetypal examples of planets, those of our solar system are merely possible outcomes of planetary system formation and evolution, and conceivably not even especially common outcomes (although this remains an open question). Here, we review the diverse range of interior structures that are both known and speculated to exist in exoplanetary systems—from mostly degenerate objects that are more than 10× as massive as Jupiter, to intermediate-mass Neptune-like objects with large cores and moderate hydrogen/helium envelopes, to rocky objects with roughly the mass of Earth.